Comparison of the impact of laparoscopic endometriotic cystectomy and vaporization on postoperative serum anti‐Mullerian hormone levels. Issue 1 (8th August 2017) - Saito, Natsuho; Yamashita, Yoshiki; Okuda, Kiyoji; Kokunai, Kana; Terai, Yoshito; Ohmichi, Masahide
Abstract: Introduction: The aim of this study was to investigate the effect of laparoscopic endometriotic cystectomy and vaporization on ovarian reserve. Methods: We prospectively analyzed the serum level of anti‐Mullerian hormone (AMH) in 62 patients at four different time points— preoperatively and at 1 month, 6 months, and 1 year postoperatively. Among the 62 cases, a bilateral cystectomy was performed in 10, bilateral vaporization in 16, a unilateral cystectomy in 24, and unilateral vaporization in 12. Results: The rate of AMH decline after unilateral cystectomy or bilateral cystectomy was higher than that after unilateral vaporization or bilateral vaporization. Age and bilaterality were associated with an AMH decline at 1 month, and age alone was associated with an AMH decline at 1 year. Moreover, being older than 38 years of age and having a revised American Society for Reproductive Medicine score >80 were independent risk factors for the non‐recovery of AMH. Conclusion: The rate of AMH decline after laparoscopic endometriotic vaporization is significantly lower than that after cystectomy. Both methods, however, have the potential to lower ovarian reserve, especially in cases of severe endometriosis or in patients older than 38 years of age.